Financing of Municipal Corporations: The process of tax imposition and financing in municipal corporations (Journal of Advances and Scholarly Researches in Allied Education, 2014)
When an urban local body desires to impose a tax, itpasses a resolution at a general meeting specifying therein, the class orclasses of persons liable to be taxed, the system of assessment to be adopted,etc. and publishes the rules so approved with a notice in the form of schedulespecified in the Act. An objection the urban local body submits such objectionswith is opinion thereon to the State Government. The State Government has thepower to sanction, modify and impose conditions relating to the levy of theproposed tax. The rules is sanctioned by the government have then to bepublished by the municipality together with a notice citing the sanction andthe date and serial number thereof. The tax may then be imposed by themunicipality from the date specified in the notice.